How to Restore Fairness After Doping Infringement? - Mika Hämäläinen (Wiley-Blackwell Publishing Ltd., 2025)
This article addresses the question how to restore the biggest possible amount of fairness after a discovery of doping infringement. I will analyse eight actions that could be taken: (1) disqualification and re-ranking, (2) change in official result, (3) medal stripping and medal re-awarding, (4) ban, (5) rematch, (6) legal action, (7) apology and (8) forgiveness. I conclude that the best way to restore the biggest possible amount of fairness seems to be a selected combination of actions. I also propose that re-ranking and medal re-awarding should be accompanied by a ceremony in which the new winners are celebrated because they typically did not have the possibility of enjoying their success in front of the original audience.